Magical Realism and Paranoia in Syed Manzoorul Islam’s “The Ground Beneath Paritosh’s Feet” and “The Merman’s Prayer” - Hasan, Shemonti; Rahim, Sifatur (Spectrum, 2022)
As far as literary genres are concerned, the relation between magical realism and paranoid fiction is diametrical. Magical realism demonstrates the supernatural elements in a mundane, secularistic fashion, without highlighting its apparent displacement. Conversely, paranoid fiction constantly forces the readers to question the reliability of the plot of a story, its characters and the storyteller as well. In short, magic realism renders the most intangible events earthly, while paranoid fiction makes a temporal situation elusive. Using two short stories — “The Ground Beneath Paritosh’s Feet” and “The Merman’s Prayer” — from Syed Manzoorul Islam’s The Merman’s Prayer and Other Stories (2013), this paper shows how employing paranoia as an agent arouses feelings of magical realism in the readers. In these stories, the writer aptly exhibits a perfect mélange of fairy tale elements as well as moments of abrupt shocks and inexplicable experiences. These stories constitute momentousness in a voluble language that produces a magical terrain where everything fantastical appears real. This paper proposes to present a detailed critique on how the elements of magical realism and paranoia are intertwined with each other in the mentioned stories. The authors draw references from dream interpretation, wish-fulfilment, psychosis and escapism to support their argument. Spectrum, Volume 16, June 2021: 82-92